Gut microbiota dynamics in a 1-year follow-up after adult liver transplantation in Northeast China - Zhang, Ruoyan; Qiu, Wei; Sun, Xiaodong; Li, Jing; Geng, Xiaochen; Yu, Shichao; Liu, Ying; Huang, Heyu; Li, Mingyue; Fan, Zhongqi; Li, Mingqian; Lv, Guoyue (Frontiers in Physiology, 2023)
Background: Liver transplantation (LTx) is the most effective treatments for end-stage liver diseases. Gut microorganisms influence the host physiology. We aim to profile the dynamics of gut microbiota in the perioperative period and one-year follow-up of LTx recipients in northeast China. Methods: 257 fecal samples were longitudinally collected from 85 LTx patients using anal swab from pre-LTx to one-year post-LTx. 48 fecal samples from end-stage liver disease patients without LTx were as control. The 16S rRNA sequencing was used to analyze gut microbiota diversity, bacterial genera, phenotype classification, and metabolic pathways. Results: The diversity of gut microbiota decreased significantly after transplant, accompanied by a profound change of the microbial structure, which characterized by increased abundance of facultative anaerobic bacteria dominated by the g_Enterococcus and reduced anaerobic bacteria composition. Predicted functional analysis also revealed disturbances metabolic pathway of the gut microbiota. After LTx, the diversity of microbiota gradually recovered but to a lesser than preoperative level after one-year recovery. Compared with pre-transplant, the microbiome structure was characterized by increase of Acidaminococcus and Acidithiobacillus after one-year transplant. Conclusion: LTx and perioperative treatment triggered gut microbial dysbiosis. The gut microbiota remodeled after-LTx to near to but significantly differed from that of pre-LTx.